IMPROVEMENT OF MARKETING MANAGEMENT IN TEXTILE ENTERPRISE (Scientific Journal of Actuarial Finance and Accounting, 2024)
This article considers the importance of marketing principles in modern management theory, revealing the content of analytical functions, determining the main directions and indicators of marketing analysis, developing ways to improve marketing analysis in manufacturing enterprises.